Pemanfaatan Sistem Cerdas Berbasis Internet of Things (IoT) untuk Optimalisasi Pengelolaan Energi di Smart Home - Muhamad Rizky Syakban Barokah; Tata Sutabri (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Today, many household appliances can connect to the internet. The technology that enables this is known as the Internet of Things (IoT). Devices such as lights, air conditioners, fans, and even power sockets can now be controlled automatically or remotely, for instance, via smartphones. In smart homes, this capability plays a significant role in helping to reduce electricity consumption.This study experimented with several simple devices such as temperature sensors, smart plugs, and timers. The goal was to examine whether these tools could effectively help lower household electricity usage. Although the system did not incorporate artificial intelligence or complex technologies, the results were still quite promising.The system was tested directly in a small house, with energy consumption carefully recorded. The findings showed a reduction in energy usage of up to 30%. Additionally, the system was able to send notifications to users, raising their awareness of their electricity usage habits. In conclusion, IoT technology can offer a simple and affordable solution for improving energy efficiency in homes.